The legacy of existence in the stories of Sana Al-Shaalan selected models - Al-Abboudi, M.M. Sana Jabbar (Tanjong Malim, 2021)
The legacy of existence in the stories of Sana Al-Shaalan selected models by Al-Abboudi, M.M. Sana Jabbar